(untitled) - Theodore V Galambos (Upper Saddle River, New Jersey, 1996)
The book provides an introduction to the properties of steel: the history of the development of steel structures; introduces and uses exclusively the LRFD method of designing steel structures; concentrates on the design of members such as tension members, beams, beam-columns, composite beams, plate girders, and then brings the pieces together in an extensive treatment of connections and frames; includes a study of both the elastic and plastic methods of desining continuous beams and frames; covers the design of open and box members for torsion, combined torsion and bending, biaxial bending, and lateral-torsional buckling. The book also has many worked examples problems, including many worked examples using SI units
Keywords: building, iron and steel,load factor design,steel, structural